Transformism, divine action in the world and the Universal Christ - Sequeiros, Leandro (Razón y fe, 2020)
The year 1920 was a very special year for Father Pierre Teilhard de Chardin (1881-1955). Not only did he turn 39, but after demobilizing from his military duties during World War I, he returned to the Jesuit community, to his training as a scientist, to his intellectual work, and to his deep spiritual life. All this happened a hundred years ago now. In 1920 we find Teilhard de Chardin settled in one of the great Jesuit communities in Paris. He was assigned to study Natural Sciences at the University of Paris and to collaborate in the famous Catholic Institute of Paris. According to the historians of science, there are two events that will mark the future of the not so young Teilhard: he is appointed professor of Paleontology and Geology at the Catholic Institute of Paris; and, thanks to the mediation of Christophe Gaudefroy (1878-1971), the philosopher and mathematician Édouard Le Roy (1870-1954) agrees to contact Teilhard.
Keywords: Teilhard de Chardin; transformism; evolution; modernism; spirituality; theology; science and religion